APL: An angle probability list to improve knowledge-based metaheuristics for the three-dimensional protein structure prediction. (December 2015) - Borguesan, Bruno; e Silva, Mariel Barbachan; Grisci, Bruno; Inostroza-Ponta, Mario; Dorn, Márcio
Abstract : Graphical abstract: Abstract : Highlights: Angle probability lists improve knowledge-based protein structure prediction methods. Development of knowledge-based methaheuristics for protein tertiary structure prediction. First principle methods with database information. Amino acid and secondary structure conformational preferences. Abstract: Tertiary protein structure prediction is one of the most challenging problems in structural bioinformatics. Despite the advances in algorithm development and computational strategies, predicting the folded structure of a protein only from its amino acid sequence remains as an unsolved problem. We present a new computational approach to predict the native-like three-dimensional structure of proteins. Conformational preferences of amino acid residues and secondary structure information were obtained from protein templates stored in the Protein Data Bank and represented as an Angle Probability List . Two knowledge-based prediction methods based on Genetic Algorithms and Particle Swarm Optimization were developed using this information. The proposed method has been tested with twenty-six case studies selected to validate our approach with different classes of proteins and folding patterns. Stereochemical and structural analysis were performed for each predicted three-dimensional structure. Results achieved suggest that the Angle Probability List can improve the effectiveness of metaheuristics used to predicted the three-dimensional structure of protein molecules by reducing its conformational search space.